Fuzzy multi-objective preventive maintenance and replacement scheduling using integer non-linear programming - Reza Alikhani; Mahmoud Saremi (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2016)
The scheduling of preventive maintenance and replacement is one of the crucial issues in the literature of system reliability and maintenance engineering. The importance of this issue is more evident in series system in which by stopping a component the whole system will stop. However, the quest of the efficient periodicity maintenance for all of component of a system which has antagonistic objectives is not a trivial task. The aim of this paper is to presenting scheduling model of preventive maintenance and replacement for series system by variable and not predetertmined periods and also by applying inflation in the model. The model is designed based on fuzzy multi-objective and integer non-linear programming. Also the proposed model is solved for a case study with numerical example and furthermore, analysis of various senarios, the effects of inflation on the model will be considered. The results show that applying inflation in the model changes not only scheduling for replacement and maintenance, but also affects the effective age of components